Eficácia do Clareamento Dental caseiro em um protocolo de aplicação pela face vestibular e palatina – Ensaio Clínico randomizado, boca dividida e cego. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
At-home bleaching is usually performed on the buccal surfaces of teeth; however, a protocol with the buccal and lingual application could increase bleaching efficacy. This randomized, single-blind, split-mouth controlled trial compared the color change, the risk and intensity of tooth sensitivity (TS), and gingival irritation (GI) of at-home bleaching applied buccal only (traditional protocol) or in the buccal and lingual surfaces (alternative protocol). Sixty patients with permanent dentition and canines A2 or darker were selected. Simple web-based randomization defined the treatment for each side of the patient's arch. The 7.5% hydrogen peroxide (FGM Dental Products®, Joinville, Brazil) was used for one h daily/14 days. The color change was evaluated at baseline, during bleaching (7 and 14 days), and one month after bleaching using shade guides scales Vita Classical and Vita Bleachedguide (VITA Zahnfabrik®, Bad Säckingen, Alemanha; ΔSGU) and a spectrophotometer Vita Easyshade (VITA Zahnfabrik®, Bad Säckingen, Alemanha; ∆Eab, ∆E00 e ∆WID). The risk and intensity of TS and GI were recorded daily using a 0-10 visual analogue scale. Patient satisfaction was evaluated with the orofacial aesthetics scale and five-point Likert scale before and after bleaching. Paired t-test, McNemar's, and Wilcoxon signed-rank test were used for data analysis ( = 5%). A whitening of approximately 12 units of ΔEab and 6.8 units of ΔSGU from Vita Classical were observed. There was no statistical difference in color change (p = 0.44), in the risk and intensity of TS (p = 0.07; p = 0.1), in the intensity of GI (p = 0.1) between the groups, but the risk of GI was higher in the traditional protocol (p < 0.002). Patient satisfaction increased after dental bleaching (p < 0.05). At-home bleaching performed in alternative protocol does not increase the whitening degree compared to traditional protocol. Clinical significance: The use of an alternative bleaching protocol does not show advantages to the treatment and to the dentist.
Keywords: Clareamento Dental; Peróxido de Hidrogênio; Clareadores dentários; Sensibilidade da dentina; Tooth whitening; Hydrogen Peroxide; Tooth Bleaching Agents; Dentin Sensitivity; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA